Abnormal default-mode network homogeneity in patients with temporal lobe epilepsy. Issue 26 (June 2018) - Gao, Yujun; Zheng, Jinou; Li, Yaping; Guo, Danni; Wang, Mingli; Cui, Xiangxiang; Ye, Wei
Abstract : Abstract: Default-mode network (DMN) plays a key role in a broad-scale cognitive problem, which occurs in temporal lobe epilepsy (TLE). However, little is known about the alterations of the network homogeneity (NH) of DMN in TLE. In the present study, we employed NH method to investigate the NH of DMN in TLE at rest. A total of 47 patients with TLE (right TLE [rTLE] 29, and left TLE [lTLE] 18) and 35 healthy controls who underwent resting-state functional magnetic resonance imaging were enrolled. NH approach was used to analyze the data. rTLE exhibited decreased NH in the right middle temporal pole gyrus and increased NH in the bilateral posterior cingulate cortex compared to the control group. In lTLE, decreased NH was observed in left inferior temporal gyrus and left hippocampus. Meanwhile, we found that lTLE had a longer performance reaction time. No significant correlation was found between abnormal NH values and clinical variables in the patients. These findings suggested that abnormal NH of the DMN exists in rTLE and lTLE, and highlighted the significance of DMN in the pathophysiology of cognitive problems occurring in TLE and also found the existence of abnormality of executive function in lTLE.